Caught in the bulimic trap? Persistence and state dependence of bulimia among young women - Michelle S. Goeree; John C. Ham; Daniela Iorio (Institute for the Study of Labor (IZA), 2011)
Eating disorders are an important and growing health concern, and bulimia nervosa (BN) accounts for the largest fraction of eating disorders. Health consequences of BN are substantial and especially serious given the increasingly compulsive nature of the disorder. However, remarkably little is known about the mechanisms underlying the persistent nature of BN. Using a unique panel data set on young women and instrumental variable techniques, we document that unobserved heterogeneity plays a role in the persistence of BN, but strikingly up to two thirds is due to true state dependence. Our results, together with support from the medical literature, provide evidence that bulimia should be considered an addiction. Our findings have important implications for public policy since they suggest that the timing of the policy is crucial: preventive educational programs should be coupled with more intense (rehabilitation) treatment at the early stages of bingeing and purging behaviors. Our results are robust to different model specifications and identifying assumptions.
urn:nbn:de:101:1-201107042739
Keywords: I12; I18; 330; bulimia nervosa; demographics; state dependence; instrumental variables; dynamic panel data estimation; addiction